(untitled) (Bangladesh Journal of Zoology, 2019)
Chengi a major river of Khagrachari district is getting polluted day by day due to unplanned river management. Both primary and secondary data have been used to conduct this work. Primary data have been collected through extensive field work, questionnaire and sample collection. Water samples have been collected from three sampling station, namely Ganjapara, Chengi Bridge and Rubber factory sites. Water temperature is higher at different sampling stations in the study site than Bangladesh standards (25°C) due to the direct hit of the sun. The maximum DO value is 5.8 mg/l at the sampling station one and the minimum is 5.3 mg/l at station three. So, it concluded that the DO value of the Chengi river is comparatively lower than the Bangladesh Standards. The water Temperature and pH is higher than the Bangladesh standards and the value of other parameters are very lower than the Bangladesh standards. In fish diversity, 10 families belonging to 6 orders were recorded and identified by the fin formula. The order Cypriniformes occupied 40%, the order Perciformes which occupies 25% and the order Beloniformes, Siluriformes, Cyprinodontiformes occupied 10% and Mollusks and other invertebrates occupied 25%, respectively in all cases. This work provides a complete picture of the water quality and also the fish diversity of the Chengi River. It will be helpful for water resource management and planning. Bangladesh J. Zool. 47(2): 343-353, 2019